Theoretical and Experimental Sets of Choice Anode/Cathode Architectonics for High-Performance Full-Scale LIB Built-up Models - Khalifa, H.; El‑Safty, S. A.; Reda, A.; Shenashen, M. A.; Selim, M. M.; Elmarakbi, A.; Metawa, H. A. (Nano-Micro Letters, 2019)
To control the power hierarchy design of lithium-ion battery (LIB) built-up sets for electric vehicles (EVs), we offer intensive theoretical and experimental sets of choice anode/cathode architectonics that can be modulated in full-scale LIB built-up models. As primary structural tectonics, heterogeneous composite superstructures of full-cell-LIB (anode//cathode) electrodes were designed in closely packed flower agave rosettes TiO2@C (FRTO@C anode) and vertical-star-tower LiFePO4@C (VST@C cathode) building blocks to regulate the electron/ion movement in the three-dimensional axes and orientation pathways. The superpower hierarchy surfaces and multi-directional orientation components may create isosurface potential electrodes with mobile electron movements, in-to-out interplay electron dominances, and electron/charge cloud distributions. This study is the first to evaluate the hotkeys of choice anode/cathode architectonics to assemble different LIB–electrode platforms with high-mobility electron/ion flows and high-performance capacity functionalities. Density functional theory calculation revealed that the FRTO@C anode and VST-(i)@C cathode architectonics are a superior choice for the configuration of full-scale LIB built-up models. The integrated FRTO@C//VST-(i)@C full-scale LIB retains a huge discharge capacity ( 94.2%), an average Coulombic efficiency of 99.85% after 2000 cycles at 1 C, and a high energy density of 127 Wh kg−1, thereby satisfying scale-up commercial EV requirements. Highlights: 1 Modulation of 3D super-scalable hierarchal anode/cathode models as choice architectonics into a full-scale LIB design. 2 The scalable architectures dynamically provide effective diffusion gateways to guarantee excellent specific LIB performance. 3 The DFT theoretical surface–surface electronic and charge map analyses confirmed the superiority of choice anode/cathode architectonics in full-scale LIB built-up models.